Fuzzy and Internal Model Control of an active suspension system for a 2-DOF vehicle model - Demir, Ozgur; Karakurt, Derya; Alarcin, Fuat (AMER INST PHYSICS, 2007)
In this study, Fuzzy-Logic-Based (FL) controller and Internal Model Control (IMC) scheme are designed for active suspension system. An aim of active suspension systems for a vehicle model is to provide good road handling and high passenger comfort by shaping the output function. The simulated system was considered to be a two-degree-of-freedom (2-DOF) model. The effectiveness of this Fuzzy Control is verified by comparison with Internal Model Control simulation results. Simulation results show that the effectiveness of the fuzzy controller is better than Internal Model Control under the same conditions.
Keywords: active suspension system; FL control; IMC; a quarter wheel vehicle; Mathematics; Physics